Young Adults’ Punctuation Error in Writing English Daily Story on Instagram - Ervin Ervin; Yuliyanah Sain; Sarjaniah Zur (Institut Agama Islam Negeri Palopo, 2022)
This research focuses on analyzing the young adult instagram users’ punctuation error on their instagram story. This present research uses qualitative design and the type is content analysis. The subjects of this research are taken from instagram users who belong to young adult instagram user and the researcher using snowball. This research employs documentation as the instrument of the study to collect the data. The findings of this research provided into 10 points; the researcher finds that there are 10 kinds of punctuation errors which are made by the young adult instagram users, they are (1) exclamation mark, (2) capital (capitalization), (3) period (full stop), (4) comma, (5) apostrophe, (6) question mark, (7) inverted comma (quotation mark), (8) ellipse, (9) hyphen, and (10) colon. The percentages of each error are exclamation mark 40.1%, capital (capitalization) 25.2%, period (full stop) 20.5%, comma 6.7%, apostrophe 2.3%, question mark 2.3%, inverted comma (quotation mark) 0.8%, hyphen 0.5%, colon 0.5%, and colon 0.2%. The findings of this study indicate that the most common punctuation error made by the young adult Instagram users was exclamation marks with a percentage of 40.1%.